Técnica, tecnologia e dilemas éticos - Pequeno, Marconi (2020)
The technique (téchnē) thought by the ancient Greeks philosophers represented the necessary doing based on ability and dexterity. It manifested a type of intellectual virtue aimed at producing something essential for the well-being of citizens and useful to the development of the pólis. Its usage has been distorted since modernity, once the technique was incorporated by technology, reaching its paroxysm in the contemporary world in the form of technocracy, mastery of nature and control of people. Such an event generated countless dilemmas and moral crossroads that nowadays encourage the debate about the possibilities, range and limits of the instrumental reason in the lives of individuals. This article addresses the transformations undergone by the technique, its incorporation by technosciences, its advances and achievements, and, finally, the ethical challenges brought by its various applications in our social context.